PENINGKATAN COUNSELOR COMPETENCE BAGI CALON GURU KELAS MI dan SD DI ERA INDUSTRI 4.0 - Roikhatul Janah; Dhiya Ayu Tsamrotul Ihtiari (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2020)
Abstract Counselor competence is the ability that must be possessed by someone to help others who have problems so the problem is clear. It becomes very important if a prospective class teacher in MI / SD must be able to have this competency. This research focuses on the study of enhancement counselor competence for prospective class teachers in MI and Elementary Schools in the industrial revolution era 4.0 which is a program created bby universities that have been granted admission to elementary schools. The method of this study a literature-based research. The results of study indicate that the Directorate of Islamic Education at the Ministry of Religion has presented all competencies that must be achieved by prospective class teachers. Managerial competence and general skills that must be possessed by prospective teachers in MI / SD classes are in accordance with the needs of a teacher in the industrial revolution era 4.0, namely counselor competence, so that prospective teachers of classes at MI / SD from Islamic tertiary institutions can be said to be able to become suitable class teachers with the industrial revolution era 4.0.   Abstrak Kompetensi konselor merupakan kemampuan yang harus dimiliki seseorang untuk membantu orang lain yang mempunyai permasalahan, sehingga permasalahan dapat terselesaikan. Menjadi sangat penting jika seorang calon guru kelas di MI/SD harus memiliki kompetensi ini. Penelitian ini memiliki fokus pada kajian tentang peningkatan counselor competence bagi calon guru kelas di MI dan SD di era revolusi industri 4.0 yang diselenggarakan oleh perguruan tinggi yang membuka program pendidikan dasar. Metode dalam penelitian ini adalah metode berbasis pustaka. Hasil penelitian ini menunjukkan bahwa Direktorat Pendidikan Islam Kementerian Agama telah menyajikan semua kompetensi yang harus dicapai oleh calon guru kelas. Kompetensi manajerial dan keterampilan umum yang harus dimiliki calon guru kelas MI/SD tersebut sesuai dengan kebutuhan seorang guru di era revolusi industri 4.0 yaitu kompetensi konselor, sehingga calon guru kelas MI/SD yang berasal dari perguruan tinggi keislaman mampu menjadi guru kelas yang sesuai dengan era revolusi industri 4.0.